2018
DOI: 10.1016/j.stem.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial: Cirmtuzumab Inhibits ROR1 Signaling and Stemness Signatures in Patients with Chronic Lymphocytic Leukemia

Abstract: Cirmtuzumab is a humanized monoclonal antibody (mAb) that targets ROR1, an oncoembryonic orphan receptor for Wnt5a found on cancer stem cells (CSCs). Aberrant expression of ROR1 is seen in many malignancies and has been linked to Rho-GTPase activation and cancer stem cell self-renewal. For patients with chronic lymphocytic leukemia (CLL), self-renewing, neoplastic B cells express ROR1 in 95% of cases. High-level leukemia cell expression of ROR1 is associated with an unfavorable prognosis. We conducted a phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(155 citation statements)
references
References 54 publications
0
144
0
Order By: Relevance
“…ROR1 is another promising target expressed by LSCs in CLL. In a recent phase 1 study involving 26 patients with R/R CLL, ROR1 inhibition with cirmtuzumab was safe and associated with inhibited CLL stemness gene expression signatures in vivo (Choi et al, 2018).…”
Section: Inhibition Of Signaling Pathways Used By Cscsmentioning
confidence: 99%
“…ROR1 is another promising target expressed by LSCs in CLL. In a recent phase 1 study involving 26 patients with R/R CLL, ROR1 inhibition with cirmtuzumab was safe and associated with inhibited CLL stemness gene expression signatures in vivo (Choi et al, 2018).…”
Section: Inhibition Of Signaling Pathways Used By Cscsmentioning
confidence: 99%
“…Indeed, a humanized monoclonal antibody, cirmtuzumab, which targets ROR1 and inhibits ROR1‐signaling in vitro has been developed 6 . A phase I study of cirmtuzumab in patients with CLL has demonstrated that this antibody can also inhibit ROR1‐signaling in vivo , suppressing leukaemia cell activation of r‐GTPases and phosphorylation of HS1 7 …”
Section: Figurementioning
confidence: 99%
“…Importantly, although ROR1 was first reported to be chronic lymphocytic leukaemia (CLL) specific, it could later also be detected in healthy tissues . It is important to stress that detection in healthy tissue might vary depending on the antibody used, since another antibody, Cirmtuzumab, was shown not to bind normal tissue when injected in primates and is currently in clinical development . A series of antibodies targeting ROR1 have been isolated from phage library and assessed for clinical use, and ROR1 2A2 CAR has been preclinically evaluated for the treatment of B‐cell malignancies .…”
Section: Igf1r and Ror1mentioning
confidence: 99%